Interpretation of religious moderation from the perspective of Muhammadiyah members in Air Joman Distric - Nurul Hidayah; Abd Rahman (Lembaga Riset Mutiara Akbar, 2026)
This study aims to analyze the interpretation of religious moderation among Muhammadiyah members in Air Joman Subdistrict, Asahan Regency, North Sumatra. Religious moderation is understood as a balanced attitude that avoids extremism and intolerance while promoting harmonious religious practices. Muhammadiyah, as one of the largest Islamic organizations in Indonesia, plays a strategic role in instilling moderate values through education, preaching, and charitable activities. However, the internalization of these values encounters challenges, particularly among the younger generation, who are increasingly influenced by social, cultural, and technological dynamics. This study employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. The research subjects consist of Muhammadiyah leaders, active members—including youth—and community members involved in Muhammadiyah activities. Data analysis is conducted through data reduction, data presentation, and conclusion drawing, supported by triangulation to ensure data validity. The findings are expected to provide insights into Muhammadiyah members’ perceptions of religious moderation, the factors shaping these interpretations, and their relevance in fostering social harmony. Ultimately, this study is expected to contribute to strengthening religious moderation within Islamic organizations and to serve as a reference for developing educational programs and policies aimed at cultivating moderate values, particularly among younger generations.